Uji Publik Rancangan Penataan Daerah Pemilihan dan Alokasi Kursi Anggota DPRD Kota Bandung Menjelang Pemilu 2024 - Mutiara Indira Yasmin (UNES Law Review, 2023)
The 2024 General Election in Indonesia is the main focus of the year's political momentum. The holding of general elections includes various stages, including the Mapping of the Electoral District Plan and the Allocation of Seats for DPRD Members. The formation of electoral districts has the main objective of strengthening political representation and achieving proportionality in accordance with geographical coverage, administrative structure and political dynamics. In preparation for the general election, the Bandung City KPU conducted public tests on the draft three times. This report provides an overview of the implementation of the public test, its results, and the conclusions drawn. The research method used is field study. Public test results show differences of opinion regarding the three electoral district designs. Stakeholders such as academics, community leaders, youth and political parties gave various responses. Public test discussions regarding the design of the Bandung City electoral district reflect the complexity and challenges in achieving adequate agreement. Some political parties and related parties prefer certain designs based on considerations of principle, stability or economics. The conclusion of the public test shows that the majority supports the Electoral District Plan. Nevertheless, all participants expressed their readiness to accept the decision of the Indonesian KPU and maintain the conduciveness of the competition. This public test provides in-depth insight into the dynamics of local politics and the complexity of electoral district structuring in the context of Indonesian democracy.